Standardization Of Beef Rendang Recipe In Jorong Padang Loweh, Nagari Suliki, Suliki District, Fifty City District - Kartika, Messy; Gusnita, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research was motivated by the ingredients used in making rendang typical of Jorong Padang Loweh which is different from rendang in general. This study aims to determine the standardization of beef rendang recipes in Jorong Padang Loweh, Nagari Suliki, Suliki District, District 50 Kota. This type of research is a mixed method (mixed method). This research was carried out in Jorong Padang Loweh in January 2022. There are two sources of data, namely: qualitative data sources, which are taken from people who are experts in making meat rending, and quantitative data sources, which are obtained from 5 limited panelists. Qualitative data collection techniques are observation, interviews, documentation, quantitative data collection techniques are organoleptic test questionnaire format. The data analysis technique uses Miles and Huberman data analysis techniques which include three flow of activities, namely data reduction (data reduction), data display (data presentation), and verification (drawing conclusions) and quantitative data analysis techniques using the formula (Mx=∑X). Based on the results of research in Jorong Padang Loweh, Nagari Suliki, Suliki District, Lima Puluh Kota Regency, researchers took beef rendang from Mrs. Yusniati's recipe including the ingredients used, the number of ingredients, how to make, and the quality of the converted Beef Rendang. After the organoleptic test results in the quality of the meat (neat), the color of the meat (brown) while the color of the bran is blackish brown, the aroma (has a distinctive aroma of rending), the texture of the meat (tender) and the bran (dry oily), this is influenced by the long cooking process. by using a fire that is not large, the taste of the meat with spices permeates and the taste of bran (savory).